STRENGTHENING MURIA COFFEE MSME THROUGH THE IMPLEMENTATION OF DIGITAL ROASTER MACHINES ON THE SLOPES OF MOUNT MURIA, RAHTAWU VILLAGE, KUDUS REGENCY - Budianita, Avira; Ariyanto, Shodiq Eko; Akhmad Zidni, Hudaya; Nita Andriyani, Budiman (International Journal of Engagement and Empowerment (IJE2), 2025)
The slopes of Mount Muria in Kudus Regency are known as one of the regions producing high-quality coffee. Coffee is a leading commodity that is utilized by the local community through various MSME activities. Several MSMEs, such as Kopi Kunci and Kopi Joesoen, have developed processed robusta coffee beans into ground coffee, marketed under local brands. However, some production processes are still carried out manually, resulting in suboptimal efficiency and productivity. To address this problem, the community service team from Muria Kudus University implemented a program to Strengthen Muria Coffee MSMEs through the Implementation of Digital Roaster Machines. The implementation of these two machines is designed to increase efficiency, production capacity, and the quality of processed coffee. The results of the activity showed a significant increase in MSME productivity and turnover, 10-fold compared to conditions before the machines were implemented. This activity is expected to strengthen the competitiveness of Muria coffee MSMEs, improve the welfare of business actors, and have a positive economic impact on the surrounding community.